PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BEI PERIODE 2015-2020 - Alifah Assa'Diyah (Journal of Fundamental Management (JFM), 2022)
This research aims to determine the effect of Current Ratio (CR), Return on equity (ROE), and Debt to Equity Ratio (DER) on firm value of companies in the cement sub-sector companies listed on the IDX for the 2015-2020 period. The population in this study was 6 cement sub-sector companies listed on the Indonesia Stock Exchange. The sample in this study was 6 companies. The data collection technique used is a documentation method by collecting materials or data related to the object of discussion. Sample selection in the study using the saturated sampling method. This research data was obtained from the Indonesia Stock Exchange. The method used in this study was panel data regression analysis with Eviews 9 software. This study proves that the Current Ratio (CR) has an insignificant negative effect on the company's value (PBV). Return on equity (ROE) has a positive and significant effect on company value (PBV). Debt to Equity Ratio (DER) has an insignificant positive effect on the value of the company (PBV)